2021
DOI: 10.15421/022187
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal efficiency of preparation based on essential oils used in aerosol disinfection in the presence of poultry

Abstract: A disinfectant was created for aerosol disinfection of premises in the presence of poultry, which will help reduce microbial contamination of premises, increase survival, weight of poultry and economic efficiency of meat production in general. The preparation based on essential oils can be used for disinfection in the presence of poultry and at the same time exhibits a therapeutic and prophylactic effect on respiratory infections. This disinfectant has a colloidal solution of silver (Ag), benzalkonium chloride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
3
0
3
Order By: Relevance
“…Essential oils as sanitizers have proven efficiency in poultry sheds. An investigation into daily aerosol air sanitization in a poultry house during broiler farming revealed that sanitization for 60 min with a formulation containing different compounds, including 0.3% thyme, eucalyptus, and fir essential oils, in a dose of 50 mL/m 3 of the room reduced the bacterial load in the air by 99%, without presenting toxicity to chickens [ 14 ]. In addition to broilers exposed to sanitization having a higher average body weight, than those not exposed, their blood tests indicated a significant increase in the amount of haemoglobin, lysozyme levels and bactericidal activity [ 14 ].…”
Section: Managing Poultry Farms With Essential Oils To Obtain Microbi...mentioning
confidence: 99%
See 2 more Smart Citations
“…Essential oils as sanitizers have proven efficiency in poultry sheds. An investigation into daily aerosol air sanitization in a poultry house during broiler farming revealed that sanitization for 60 min with a formulation containing different compounds, including 0.3% thyme, eucalyptus, and fir essential oils, in a dose of 50 mL/m 3 of the room reduced the bacterial load in the air by 99%, without presenting toxicity to chickens [ 14 ]. In addition to broilers exposed to sanitization having a higher average body weight, than those not exposed, their blood tests indicated a significant increase in the amount of haemoglobin, lysozyme levels and bactericidal activity [ 14 ].…”
Section: Managing Poultry Farms With Essential Oils To Obtain Microbi...mentioning
confidence: 99%
“…An investigation into daily aerosol air sanitization in a poultry house during broiler farming revealed that sanitization for 60 min with a formulation containing different compounds, including 0.3% thyme, eucalyptus, and fir essential oils, in a dose of 50 mL/m 3 of the room reduced the bacterial load in the air by 99%, without presenting toxicity to chickens [ 14 ]. In addition to broilers exposed to sanitization having a higher average body weight, than those not exposed, their blood tests indicated a significant increase in the amount of haemoglobin, lysozyme levels and bactericidal activity [ 14 ]. The nebulization of 0.5 mL of an aqueous solution of Mentha piperita or Thymus vulgaris essential oil at a concentration of 1:500 to 1:250 in poultry houses was proven effective in reducing the bacterial and fungal load in the air, drinkers, walls and/or litter [ 7 , 8 ].…”
Section: Managing Poultry Farms With Essential Oils To Obtain Microbi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Миючі властивості та пролонгована бактерицидна дія при дезінфекції залежить від поверхневого натягу розчину. На даний час науковці звертають увагу на розробку та впровадження засобів на основі йоду (Kovalenko & Nedosiekova, 2011;Ponomarenko et al, 2021).…”
Section: вступunclassified
“…Результати досліджень препарату "Біолайд" підтвердили попередні дослідження щодо застосування дезінфікуючого засобу у присутності пти-ці. Встановлена певна кореляція показників резистентності птиці до дезінфектантів та їхній вплив на мікроорганізми в приміщенні (Ponomarenko et al, 2021).…”
Section: таблицяunclassified